The Constitutional Law of Incarceration, Reconfigured - Schlanger, Margo (2018)
On any given day, about 2.2 million people are confined in U.S. jails and prisons—nearly 0.9% of American men are in prison, and another 0.4% are in jail. This year, 9 or 10 million people will spend time in our prisons and jails; about 5000 of them will die there. A decade into a frustratingly gradual decline in incarceration numbers, the statistics have grown familiar: We have 4.4% of the world’s population but over 20% of its prisoners. Our incarceration rate is 57% higher than Russia’s (our closest major country rival in imprisonment), nearly four times the rate in England, and over ten times the rate in Nordic and Scandinavian countries. And while American jails and prisons are less brutal and unhealthy now than they were in the 1970s (when the total incarcerated population was under half a million people), current conditions behind bars are sometimes horrendous